Enhancing arabic morphology learning for beginners: the effectiveness of the eclectic method in modern islamic boarding school - Ajie, Syahrani Dewi; Sopian, Asep; Khalid, Shofa Musthofa (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
For beginner learners of Arabic, morphology is difficult to master because of many changes in word form, so an appropriate learning method is needed to make learning more effective. This research intends to test the effectiveness of the eclectic method in learning Arabic morphology for beginners. This research uses a quantitative method, the design used is a quasi-experiment design with the type of nonequivalent control group design. The data comes from the pretest and the posttest outcomes. The data is analyzed using descriptive statistics and non-parametric statistics. The samples in this research are 42 students of class VIII A and B of Manāhij As-Sādāt Modern Boarding School. The results of this research show that the eclectic method average is 65.14% which means it is quite effective to be used in learning morphology for beginners. The results of this research are expected to provide more information about the variation of learning methods that can be used to learn Arabic morphology. Teachers are expected to apply the eclectic method by combining all language skills in one learning time; listening, reading, writing, and speaking so that learning becomes more effective.